A grand unified model for liganded gold clusters - Wen Wu Xu (Nature Portfolio, 2016)
There is no one theoretical model that can explain the stability of all known liganded gold clusters. Here, the authors present a grand unified model, inspired by the quark model of particle physics, which describes gold clusters as combinations of stable triangular Au3(2e) and tetragonal Au4(2e) ‘composite particles’ built from gold atom ‘elementary particles’.